Developing higher-order thinking skill (HOTS) test instrument using Lombok local cultures as contexts for junior secondary school mathematics - Syukrul Hamdi; Iin Aulia Suganda; Nila Hayati (REID (Research and Evaluation in Education), 2018)
The study was aimed at producing a valid and reliable higher-order thinking skill (HOTS) test instrument using Lombok local cultures as contexts in the junior secondary school mathematics subject matter. The study is developmental research involving a field try-out of 75 students of Grade VIII. Data were analyzed using classical test theories of difficulty levels, discriminating powers, and functioning distractors. The test validity is assessed using the Aiken formula and reliability is estimated by Cronbach Alpha. Findings show that, of the 20 initial multiple-choice items, 15 were valid and reliable and had the characteristics of good test items with a medium-rated difficulty level average of 0.28, a good-rated discriminating power of 0.31), a good-rated reliability coefficient of 0.79, and all distractors well-functioning.